An analysis of the three-dimensional kinetics and kinematics of maximal effort punches among amateur boxers - Stanley, E.; Thomson, E.; Smith, G.; Lamb, K. L. (International Journal of Performance Analysis in Sport, 2018)
The purpose of this study was to quantify the 3D kinetics and kinematics of six punch types among amateur boxers. Fifteen males (age: 24.9 ± 4.2 years; stature: 1.78 ± 0.1 m; body mass: 75.3 ± 13.4 kg; boxing experience: 6.3 ± 2.8 years) performed maximal effort punches against a suspended punch bag during which upper body kinematics were assessed via a 3D motion capture system, and ground reaction forces (GRF) of the lead and rear legs via two force plates. For all variables except elbow-joint angular velocity, analysis revealed significant (P < 0.05) differences between straight, hook and uppercut punches. The lead hook exhibited the greatest peak fist velocity (11.95 ± 1.84 m/s), the jab the shortest delivery time (405 ± 0.15 ms), the rear uppercut the greatest shoulder-joint angular velocity (1069.8 ± 104.5°/s), and the lead uppercut the greatest elbow angular velocity (651.0 ± 357.5°/s). Peak resultant GRF differed significantly (P < 0.05) between rear and lead legs for the jab punch only. Whilst these findings provide novel descriptive data for coaches and boxers, future research should examine if physical and physiological capabilities relate to the key biomechanical qualities associated with maximal punching performance.